Annual Report 2021 of Current Applied Science and Technology - Dusanee Thanaboripat (My University, 2021)
Current Applied Science and Technology journal (formerly KMITL Science and Technology Journal) has been published by King Mongkut’s Institute of Technology Ladkrabang (KMITL) since its inception as KMITL Science Journal in 2001. In July 2017, the title of journal has been changed to Current Applied Science and Technology and printed online only. The journal is an open access peer-reviewed and double blinded journal which publishes online original academic research and review articles in the fields related to applied science and technology. Current Applied Science and Technology journal was submitted to Scopus database on 3 December 2018 via TCI-TRF-Scopus Collaboration Project and the journal was accepted to be indexed in Scopus on 14 January 2019. At present the journal is currently under the responsibility of the Office of Academic Journal Administration, President’s Office, KMITL, Thailand. Apart from indexing in Scopus, the journal is also indexing in ACI (ASEAN Citation Index), TCI (Thai Citation Index) Tier 1 and Scimago Journal Rank (SJR): Q4. The journal provides a service called Advanced Online Publication (AOP) or Online First Publication, which is beneficial to both the authors and the readers and there is no page charge for submission. All articles can be freely downloaded from the journal website: https://li01.tci-thaijo.org/index.php/cast.
Keywords: Web of science; Impact factor; Open access journal; null